Inkulturasi Musik Etnik dalam Liturgi Gereja Kalimantan Evangelis, Kalimantan Tengah - Sugiyanto Sugiyanto (JURNAL TERUNA BHAKTI, 2022)
The inculturation of ethnic music is an inevitability to serve as a suggestion of the ministry of God's Word in the liturgy. This research uses qualitative methods that use ethnographic research to solve problems. The data source is GKE liturgical figures, musicians, and practitioners of ethnic music GKE who have carried out ethical music in worship. The Book of Oneness Song which has become a liturgical chant is accepted at GKE. The results showed that in the concept of theological musical sequestration, GKE accepts all types of ethnic musical instruments such as rebabs, harps, drums, knobs, distillers, and words as musical instruments that can be used to praise God. The concept of theological and practical inculturation is that all ethnic chants that can enter the GKE liturgy are ethnic songs whose lyrics are taken from the Bible, the result of its own creation that has spiritual value. Translated songs, transfers, and new creations that are measured and meaningful to the Christian faith. Ungkup singing is processed through the stage of inculturation in the form of transferring lyrics into Dayak Ngaju language that is adapted to song notations originating from the West including those from Indonesia. Tumet Leut Basa Maanyan's singing has been processed through the inculturation stages of new creations. Namely, the cultural elements contained in it are concocted with new and spiritual elements so that they enter the liturgy of the Maanyan Dayak Tribe GKE. AbstrakInkulturasi musik etnik merupakan suatu keniscayaan untuk dijadikan sebagai saran pelayanan Firman Tuhan dalam liturgi. Penelitian ini menggunakan metode kualitatif yang menggunakan penelitian etnografi untuk memcahkan masalah. Sumber data adalah tokoh Liturgi GKE, musisi, praktisi musik etnik GKE yang pernah melaksanakan musik etik dalam ibadah. Buku Kidung Keesaan yang telah menjadi nyanyian liturgis yang diterima di GKE. Hasil penelitian menunjukkan bahwa konsep inkulutrasi musik secara teologis, GKE menerima semua jenis alat musik etnik seperti rebab, kecapi, gendang, kenong, suling, katambung sebagai alat musik yang bisa dipergunakan untuk memuji Tuhan. Konsep inkulturasi secara teologis dan praktis, bahwa semua nyanyian etnik yang dapat masuk ke dalam liturgi GKE adalah lagu-lagu etnik yang lirik-liriknya diambil dari nas Alkitab, hasil ciptaan sendiri yang memiliki nilai rohani. Lagu-lagu terjemahan, pemindahan dan kreasi baru yang terukur dan bermakna bagi iman Kristen. Nyanyian Ungkup diproses melalui tahapan inkulturasi berupa pemindahan lirik-lirik ke dalam Bahasa Dayak Ngaju yang disesuaikan dengan notasi-notasi lagu yang berasal dari Barat termasuk yang berasal dari Indonesia. Nyanyian Tumet Leut Basa Maanyan telah diproses melalui tahapan inkulturasi kreasi baru. Yakni, unsur kebudayaan yang terkandung di dalamnya diramu dengan unsur-unsur baru dan rohani sehingga masuk liturgi GKE Suku Dayak Maanyan.